2018
DOI: 10.1186/s12913-018-2943-y
|View full text |Cite
|
Sign up to set email alerts
|

Selling my sheep to pay for medicines – household priorities and coping strategies in a setting without universal health coverage

Abstract: BackgroundThe first month of life is the period with the highest risk of dying. Despite knowledge of effective interventions, newborn mortality is high and utilization of health care services remains low in Ethiopia. In settings without universal health coverage, the economy of a household is vulnerable to illness, and out-of-pocket payments may limit families’ opportunities to seek health care for newborns. In this paper we explore intra-household resource allocation, focusing on how families prioritize newbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 33 publications
2
43
0
Order By: Relevance
“…The health care effectiveness largely depends on the socio-economic aspects of the family/household [25]. Six and four studies reported that there was a positive relationship between CBHI, and being male [20,38,42,43,46,47] and female [15,21,37,40] headed of the households respectively.…”
Section: Demographic and Socio-economic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The health care effectiveness largely depends on the socio-economic aspects of the family/household [25]. Six and four studies reported that there was a positive relationship between CBHI, and being male [20,38,42,43,46,47] and female [15,21,37,40] headed of the households respectively.…”
Section: Demographic and Socio-economic Factorsmentioning
confidence: 99%
“…If CBHI is not in place, households face catastrophic OOP expense through borrowing to cover direct and indirect health care costs. For those who are unable to get money, it is unthinkable to take health care [25]. Hence, with no any risk pooling mechanism, households face impoverishment from OOP expense [26].…”
Section: Introductionmentioning
confidence: 99%
“…24 There is a lack of knowledge of how patients obtain cancer diagnosis and treatment in a system where the financial burden for patients is enormously tangible and where self-help strategies and informal practices are widespread. [25][26][27][28] To fill this gap in our knowledge, our study explores how patients cope with the failures in the system of oncology treatment in Ukraine. We thus illustrate oncopatient's experiences and the strategies that are used by the patients themselves, and their family members-carers, as a response to the financial and organizational barriers to cancer treatment, so-called coping strategies.…”
Section: Funding Informationmentioning
confidence: 99%
“…This study uses data from key stakeholder groups: physicians, patients, representatives of pharmaceutical companies, and charitable foundations. It builds on and expands the existing literature on coping strategies and informal practices 27,28,30 as well as on out-of-pocket payments for cancer treatment using qualitative methodologies, 8 and it is organized as follows. The next section provides information on the organization and financing of health care services in Ukraine with a focus on cancer diagnostics and treatment.…”
Section: Funding Informationmentioning
confidence: 99%
See 1 more Smart Citation